THE INFLUENCE OF CELEBRITY ENDORSERS ON PURCHASING DECISIONS FOR SCARLETT SKINCARE (A CASE STUDY ON A STUDENT OF MANAGEMENT DEPARTMENT, FACULTY OF ECONOMICS AND BUSINESS, MAKASSAR STATE UNIVERSITY) - Andi Hasfira; Uhud Darmawan Natsir, Muh. Ichwan Musa, Muhammad Ilham Wardhana Haeruddin (ADISAM Publisher, 2022)
This study aims to determine the influence of celebrity endorser on purchasing decisions for Scarlett Skincare products. The sample is determined by means of a purposive sampling technique, meaning that it is determined by considering the research objectives based on the criteria that have been determined beforehand. The sample in this study was 100 respondents. Data collection techniques were carried out by means of observation, interviews, and questionnaires. The data analysis technique consisted of a validity test, reliability test, classical assumption test consisting of normality test, multicollinearity test, and heteroscedasticity test, simple regression analysis test, and hypothesis testing. The results showed that the celebrity endorser had a positive and significant influence on the Scarlett Skincare Purchase Decision in Management Department Students, Faculty of Economics and Business, UNM. Based on the results of the t test of 43.090> 1.984 and the value of 0.000 < 0.05 with an R Square of 0.950, it shows about 95% of the celebrity endorser indicators with the most dominant influence being the attraction indicator. Meanwhile, the indicator of purchase decision with the most dominant influence is the indicator of decision on the choice of time.